Compressive behaviors of ultra-low-weight foamed cement-based composite reinforced by polypropylene short fibers. (August 2020) - Yang, Yuanyi; Zhou, Qi; Deng, Yi; Lin, Jinhui
With advantages in sustainability, low thermal conductivity, and self-weight, the foamed cement-based composites have captured tremendous attention in various low strength structural and nonstructural applications. This paper aimed to investigate the effects of the short polypropylene fibers on the quasi-static compression performance of the ultra-low-weight foamed cement-based composites. The results show that the elasticity modulus, peak strength, and ultimate linear strength of the fiber-reinforced composites are increased by 208%, 42%, and 71%, respectively. The plateau stress and the densification strain energy of fiber-reinforced composites are improved by up to 49% and 47%. Simultaneously, the failure mode of the fibrous sample is altered from a brittle behavior to plastic behavior. The significance of this work shows that short synthetic fibers can improve the compressive capacity considerably, turning out to be an effective strategy for obtaining higher mechanical strengths associated with ultra-low-weight typical cement-based elements. According to the experiment results, a constructive damage model is carried out to describe the compressive properties of short PP fiber-reinforced composites. Thus, such theoretical curves can describe the compression behavior successfully and can be potentially applied in practical project and numerical simulation. This work can also be useful toward the foundation of optimal design for toughening behavior in fiber-reinforced lightweight cement elements.